Mixed Fuzzy-Logic and Game-Theoretical Approach to Justify Vehicle Models for Servicing the Public Bus Line - Vitalii Naumov; Laura Bekmagambetova; Zukhra Bitileuova; Zhumazhan Zhanbirov; Igor Taran (Communications - Scientific letters of the University of Zilina, 2022)
One of the main problems to be solved by the transport operators is the substantiation of the vehicle models servicing the transport lines. A gametheoretical approach is proposed in this paper to justify the bus model choice based on the passengers’ preferences and the structure of the passenger flows. To estimate the customers’ preferences, the membership functions for fuzzy sets of the optimal vehicle models were defined. The simulation experiment aiming to estimate the city fleet structure in terms of the vehicles’ capacity was conducted for the Talas city (Kazakhstan) based on the proposed approach with use of the corresponding software implementation of the developed mathematical models. As a result of the experimental studies, the impact of the passengers’ flow structure and the number of carriers on the rational structure of the city bus fleet was studied in the paper.